1996
DOI: 10.1097/00007890-199610270-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Hydroxyl Radical Scavenger (Nicaraven) in Recovery of Cardiac Function Following Preservation and Reperfusion1

Abstract: We investigated the efficacy in reducing myocardial preservation and reperfusion (P/R) injury of direct hydroxyl radical scavenging by nicaraven as compared with scavenging of both superoxide radicals and hydrogen peroxides by superoxide dismutase (SOD) and catalase (CAT), respectively. Isolated rat hearts were mounted on a Langendorff (L) apparatus to estimate the baseline aortic flow (AF), coronary flow (CF), cardiac output (CO), systolic pressure (SP), aortic mean pressure (MP), rate pressure product, and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…1,14 The cell protects itself by ubiquitous endogenous free radical scavengers, which may be depleted by ischemia and additionally overwhelmed by the burst of free radical production that occurs with the onset of reoxygenation or hyperoxia after reperfusion with aortic unclamping during CPB. 15 Prasad et al have shown that superoxide dismutase and catalase, which are scavengers of superoxide anion and hydrogen peroxide, respectively, are effective in preventing postpump cardiac dysfunction, 14 16 The present study showed that lowering the reperfusate PO2 after aortic unclamping on CPB reduced oxidative myocardial damage and the effects on the hemodynamics and myocardial enzyme release persisted for approximately 3 h after discontinuation of CPB. In fact, the CI in the lowering reperfusate PO2 group was higher than in the hyperoxic reperfusion groups at 30 min and 3 h after discontinuation of CPB.…”
Section: Discussionsupporting
confidence: 53%
“…1,14 The cell protects itself by ubiquitous endogenous free radical scavengers, which may be depleted by ischemia and additionally overwhelmed by the burst of free radical production that occurs with the onset of reoxygenation or hyperoxia after reperfusion with aortic unclamping during CPB. 15 Prasad et al have shown that superoxide dismutase and catalase, which are scavengers of superoxide anion and hydrogen peroxide, respectively, are effective in preventing postpump cardiac dysfunction, 14 16 The present study showed that lowering the reperfusate PO2 after aortic unclamping on CPB reduced oxidative myocardial damage and the effects on the hemodynamics and myocardial enzyme release persisted for approximately 3 h after discontinuation of CPB. In fact, the CI in the lowering reperfusate PO2 group was higher than in the hyperoxic reperfusion groups at 30 min and 3 h after discontinuation of CPB.…”
Section: Discussionsupporting
confidence: 53%
“…Consistent with this notion, Ku et al (27,28) reported that formation of OH ⅐ from O 2 •Ϫ and H 2 O 2 is likely responsible for injury due to cold storage, and addition of nicaraven (OH ⅐ scavenger) to the preservation solution protected against the injury.…”
Section: Discussionmentioning
confidence: 83%
“…2,8 Beckman et al reported that superoxide anion and NO interact to form cytotoxic oxygen species, 12 and NO generation is also dependent on the PO2. 13 Some studies have shown that free radical scavengers attenuate reperfusion injury following ischemia, [8][9][10][11][14][15][16] so we hypothesized that as an alternative to treatment with antioxidants, it is conceivable that the production of oxygen-derived free radicals could be avoided by lowering the PO2 after ischemia. Carla et al reported that hyperoxic reperfusion did not increase myocardial infarct size as an irreversible change, but they did not mention arrythmias or myocardial functional stunning as reversible changes.…”
Section: Discussionmentioning
confidence: 99%
“…5 In the case of myocardial stunning, the phenomenon may be mediated, at least in part, by a burst of free radicals formed during the early phase of reperfusion and improved by free radical scavengers at the time of reperfusion. [6][7][8][9][10] As an alternative treatment to antioxidants, it is conceivable that adequate physiologic oxygen tension during reperfusion following ischemia may limit oxidative injury. Thus, we hypothesized that the production of oxygenderived free radicals may be attenuated by sustaining a more physiologic oxygen tension (PO2) during reperfusion following ischemia.…”
mentioning
confidence: 99%